Speech aphasia according to Roman Jakobson (a linguistic study) - djemiat, .yazid; Sagheer, salem (El Omda in Linguistics and Discourse Analysis, 2025)
Roman Jakobson is considered one of the leading figures in modern linguistic research. He addressed several linguistic issues, including the study of speech pathology, in which he examined aphasia from both a clinical and linguistic perspective among affected individuals. He also conducted numerous anatomical studies that enabled him to identify different types of aphasia. In this study, we aim to clarify Jakobson’s linguistic approach to aphasia, where he relied on several binary oppositions to analyze two fundamental aspects of language: selection (substitution) and combination (composition). He also distinguished two types of aphasic disorders: similarity disorder and contiguity disorder, while explaining their causes, forms of expression among patients, and linguistic methods of treatment.